2022
DOI: 10.1007/s12310-022-09525-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Secondary Traumatic Stress and Compassion Fatigue in Teachers

Abstract: When teachers care for children with trauma histories, they are at risk of developing compassion fatigue (CF), or a reduced empathic capacity (Hupe and Stevenson in J Child Custody Res Issues Pract 16(4):364–386, 2019. https://doi.org/10.1080/15379418.2019.1663334 ). They may also develop secondary traumatic stress (STS), a secondary condition resulting from a person learning about details of a traumatic event experienced by someone in their care (Essary et al. in Kappa Delta Pi Record 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
0
40
0
2
Order By: Relevance
“…Research on the EBS strains have shown high levels of EBS among school personnel, including teachers, akin to levels found among mental health workers (Borntrager et al, 2012;Ormiston et al, 2022). Teachers who continuously work with students who have a history of trauma or hear about students' trauma experiences may experience EBS (Figley, 1995) Symptoms similar to PTSD, but from secondary exposure Secondary traumatization, secondary traumatic stress disorder Compassion fatigue Acute, affective phenomenon engendering high levels of stress after trauma exposure (Figley, 1995) Symptoms parallel original trauma victim's (e.g., avoidance, hyperarousal, numbing, sleep disturbances)…”
Section: Defining Empathy-based Stressmentioning
confidence: 99%
“…Research on the EBS strains have shown high levels of EBS among school personnel, including teachers, akin to levels found among mental health workers (Borntrager et al, 2012;Ormiston et al, 2022). Teachers who continuously work with students who have a history of trauma or hear about students' trauma experiences may experience EBS (Figley, 1995) Symptoms similar to PTSD, but from secondary exposure Secondary traumatization, secondary traumatic stress disorder Compassion fatigue Acute, affective phenomenon engendering high levels of stress after trauma exposure (Figley, 1995) Symptoms parallel original trauma victim's (e.g., avoidance, hyperarousal, numbing, sleep disturbances)…”
Section: Defining Empathy-based Stressmentioning
confidence: 99%
“…Secondary traumatic stress and Compassion Fatigue (CF) emerged as constructs from the healthcare and mental health professions (Sinclair et al, 2017) and have recently begun to be examined in the teaching context (Ormiston et al, 2022). Cieslak et al (2014) define CF as "a reduced empathic capacity or client interest manifested through behavioral and emotional reactions from exposure to traumatizing experiences of others" (p. 76).…”
Section: Defining Burnout Secondary Traumatic Stress Compassion Fatig...mentioning
confidence: 99%
“…Training in TIP in schools has also been shown to mitigate CF and STS levels in teachers (Peterson, 2019;Christian-Brandt et al, 2020;Anderson et al, 2021). In their systematic literature review on STS and CF in teachers, Ormiston et al (2022) suggested a two-pronged approach of creating a school system that enabled teachers to receive training and education related to TIP as well as creating a clear system of interagency collaboration with schools to provide opportunities for students to receive any interventions from mental-health specialists that they may need. They found that studies which looked at schools with these two approaches reported more positive feedback from teachers overall, although few studies explicitly linked TIP training with intent to leave the profession.…”
Section: Trauma Awareness and Self-efficacy Of Teachers And How It Im...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to traumatized students has been shown to have negative effects on teachers’ well-being and mental health (Rankin, 2021; Yang, 2021). Ormiston et al (2022) indicated that compassion satisfaction and compassion fatigue are important factors to consider when assessing the impact of exposure to traumatized children on adults.…”
Section: Compassion Fatigue–compassion Satisfaction Theorymentioning
confidence: 99%